The Impact of US Uncertainty Shocks on Small Open Economies - Pär Stockhammar; Pär Österholm (Örebro University School of Business, 2016)
In this paper, we investigate the impact of US uncertainty shocks on GDP growth in nine small open economies: Australia, Canada, Denmark, Finland, Iceland, New Zealand, Norway, Sweden and the United Kingdom. We compare the impact of two types of shocks: i) stock market volatility shocks and ii) policy uncertainty shocks. Using quarterly data from 1986Q1 to 2016Q1, this issue is analysed using Bayesian VAR models. Our results suggest that policy uncertainty seems to matter more than stock market volatility. Stock market volatility shocks appear to robustly have significant effects on Danish GDP growth. Policy uncertainty shocks, on the other hand, reliably lowers GDP growth in all five Nordic countries in a statistically significant manner. Statistically significant effects of policy uncertainty shocks on the Anglo-Saxon countries in our sample are harder to establish and are, in our preferred specification, only found for the United Kingdom.
Keywords: C32; F43; 330; VXO; Policy uncertainty; Bayesian VAR; Spillovers